A sustainable framework for spatial planning of photovoltaic solar farms using GIS and multi-criteria assessment approach in Central Anatolia, Turkey. (March 2021) - Tercan, Emre; Eymen, Abdurrahman; Urfalı, Tuğrul; Saracoglu, Burak Omer
Highlights: A combination of AHP, WLC, and IDW methods are used in a GIS environment. Complex and contradictory 17 evaluation criteria are considered to find the convenient PV farms locations. The western region of the study area has an excellent solar energy potential. Most of the existing PV farms locations frequently match up with the convenient zones presented in this study. Abstract: Convenient photovoltaic (PV) solar farms location choosing is a substantial issue in terms of renewable energy policies and spatial planning. This study is carried out to contribute to the growth, expansion, advancement, and location selection of PV farms using Geographical Information System (GIS), Analytic Hierarchy Process, Weighted Linear Combination, and Inverse Distance Weighting approaches. All maps were prepared for 17 evaluation criteria and suitability classification in GIS environment in the province of Kayseri (Turkey). Global Horizontal Irradiation was identified to be the most essential sub-criteria, followed by aspect, land use/cover, slope, distance from power network, temperature, precipitation, total snowy days, relative humidity, distance from land transportation network and others. The results show that an extensive percentage (3.70 % of the study area is highly suitable, and 40.01 % is moderately suitable) of the study area has a unique capacity for the establishment of PV farms. The results indicate that the western region of the study area is the most convenient for the installation of PV farms. In this study, the location selection decisions of existing PV farms investments were evaluated. Most of the existing PV farm's locations frequently match up with the convenient zones presented in this study. This study provides a considerable, utility, and sustainable framework for spatial planning of PV farms in order to develop regional renewable energy and environmental conservation policies and to raise the awareness of the public.